Correlation Between Self-Efficacy and Students’ Mathematical Communication Skills - Nadila Destriani; Undang Indrajaya (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study is motivated by the low level of students’ mathematical communication skills and the suboptimal level of self-efficacy, both of which require special attention in the learning process. Mathematical communication skills are essential as they enable students to express and interpret mathematical ideas clearly, both orally and in writing. Self-efficacy plays an important role in shaping students’ confidence to actively participate, complete tasks, and express their opinions. This study aims to determine the relationship between self-efficacy and students’ mathematical communication skills using a quantitative approach with a correlational method. The participants were 25 eighth-grade students of SMPN 5 Tarogong Kidul selected through purposive sampling. The research instruments consisted of a self-efficacy questionnaire and a mathematical communication skills test based on the indicators of each variable. The data were analyzed using Pearson correlation analysis. The results showed a correlation coefficient of 0.544 with a significance value of 0.005, indicating a positive and significant relationship between self-efficacy and students’ mathematical communication skills. These findings suggest that higher levels of self-efficacy are associated with better ability in communicating mathematical ideas. This study also contributes by providing a comprehensive analysis supported by prerequisite statistical tests, thereby strengthening empirical evidence regarding the relationship between the two variables at the junior high school level. Therefore, affective aspects, particularly self-efficacy, need to be considered in improving the effectiveness of mathematics learning through supportive and interactive learning strategies.